The application using value stream mapping for efficiency increasing logistics and supply chain of rice management in northeastern area of Thailand - Thoucharee, Sanan; Pitakaso, Rapeepan (Asia-Pacific Journal of Science and Technology, 2017)
This research has applied value stream mapping for waste analyzing in Logistics and Supply Chain of Rice Management in Northeastern Area of Thailand. We found that the waste that occurred was time for activity paddy collecting in the warehouse of agricultural- cooperative warehouse, paddy collecting and rice in the warehouse of the mills, agricultural - cooperative warehouse, and rice warehouse of exporters. So that it should focus on the activity management will reduces time and cost of logistics in the routes is routes farmers - rice mills & agricultural cooperative – yong – exporter time decreased 67.12% costs decreased 4.42%, routes farmers - agricultural cooperative - rice mills & agricultural cooperative -yong– exporter time decreased 76.00% costs decreased 5.71%, routes farmers - middleman -rice mills & agricultural cooperative – yong - exporter time decreased 67.08% costs decreased 4.34%, routes farmers – groups of farmers - middleman - rice mills & agricultural cooperative -yong – exporter time decreased 67.05% costs decreased 4.30%, routes farmers – central market -middleman -rice mills & agricultural cooperative -yong– exporter time decreased 66.99% costs decreased 4.09%. The cost and time decrease will affect the increasing the whole effectiveness of the logistics process and rice supply chain.